Synthesis and Membrane Properties of Troger′s Base Polymers - HUANG Ronglu; ZHANG Chen; WANG Yuyong; TANG Hai; ZHANG Ze (Nantong Daxue xuebao. Ziran kexue ban)
Troger′s base polymers have strong chemical stability, thermal stability and rigidity, V-shaped ladder structure and porous structure. The nitrogen heterocyclic ring is hydrophilic. Therefore, they are significant materials for the membranes with high water flux. Furthermore, the nitrogen-containing bridge ring in Troger′s base polymers can be hydrolyzed into diazohetercyclic octane skeleton bearing strong hydrophilicity under certain conditions. The water flux and rejection of the corresponding membrane can be adjusted by changing the ratio of opened ring. Therefore, several Troger′s base polymers with different ring opening ratios are successfully synthesized by controlling the ring opening conditions in the present work. Then the corresponding membranes are prepared from these polymers, and the morphology, water flux, interception rate, anti-pollution rate and porosity of the membranes are systematically investigated. The effects of the polymers′ structure resulted from ring opening ratios on the properties of the membranes are analyzed and discussed. The results show that the opening of Troger′ s base polymer has the significant effects on the membrane properties. The properties of the membranes after ring opening have been significantly improved, which provides a potential way for improving the properties of TB film materials and expanding its application.